The role of occupational safety in road works: Implementation of preliminary risk analysis in the execution of asphalt resurfacing (Research, Society and Development, 2023)
The aim of this research is to present, through the application of a risk analysis technique, a mapping of dangerous occurrences, the causes and consequences of the risks to which highway construction workers are exposed, as well as to recommend appropriate control measures for the case study investigated. A photographic survey was carried out on a critical stretch of road resurfacing work located on Avenida Dona Otília, in the São Pedro district of Manaus/AM. The Preliminary Risk Analysis (APR) technique was used to draw up a qualitative and quantitative opinion of each function included in the construction work process, with the aim of diagnosing the risks and finding improvements in the working conditions at each position, with a view to the well-being and protection of workers' lives. However, the survey indicated a higher incidence of physical risks, especially in the role of paver operator. It is therefore necessary to introduce an accident prevention policy, training workers to recognize potentially dangerous situations before accidents or near misses occur, and to keep records of both. Another important measure is to check the condition of EPI and implement equipment control sheets. The risk of being run over was observed in all functions, and it is important that there is adequate signage for employees on the road, the works and the maximum speed allowed on these stretches.